„Nigdy więcej!” – historia pewnej utopii - Buryła, Sławomir (Poznańskie Studia Polonistyczne. Seria Literacka, 2015)
The author of the article studies the literary and cultural topos “Never more!”. He discusses its social and historical contexts as well as the instrumentalization of the anti-war rhetorics in the period of Peoples’ Republic of Poland (Pol. abbr. PRL). The outline also presents the place of anti-war rhetorics in the modern culture.